2004
DOI: 10.1111/j.1523-1755.2004.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a local tissue angiotensin system in podocytes by mechanical strain11See Editorial by Kriz, p. 333.

Abstract: Mechanical strain leads to up-regulation of the AT1R and increased angiotensin II production in conditionally immortalized podocytes. The resulting activation of a local tissue angiotensin system leads to an increase in podocyte apoptosis, mainly in an AT1R-mediated fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
245
2
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(268 citation statements)
references
References 38 publications
15
245
2
4
Order By: Relevance
“…16 Cultured podocytes exposed to mechanical stress enhance angiotensin II type 1 receptor gene expression, which results in podocyte injury. 17 In the present study, the desmin staining score, which shows the degree of damaged podocytes, was significantly reduced by irbesartan. These previous observations, along with the findings of our study, show that blockade of angiotensin II is useful for attenuation of glomerulosclerosis and proteinuria in DS rats after high salt loading.…”
Section: Discussionsupporting
confidence: 55%
“…16 Cultured podocytes exposed to mechanical stress enhance angiotensin II type 1 receptor gene expression, which results in podocyte injury. 17 In the present study, the desmin staining score, which shows the degree of damaged podocytes, was significantly reduced by irbesartan. These previous observations, along with the findings of our study, show that blockade of angiotensin II is useful for attenuation of glomerulosclerosis and proteinuria in DS rats after high salt loading.…”
Section: Discussionsupporting
confidence: 55%
“…These findings indicate that under pathologic conditions, an upregulation of chymase occurs and increased local AngII generation cannot be attenuated by ACE inhibitors. Mechanical stress of podocytes stimulates local AngII synthesis by non-ACE pathways that presumably involve chymase (6), yet the exact role of chymase-mediated AngII formation for renal disease in humans is unclear, and ACE inhibitors clearly slow progression of disease.…”
Section: Generation Of Angii and Other Peptidesmentioning
confidence: 99%
“…58 Studies in cultured podocytes have demonstrated that these cells possess an independent renin-Ang system (RAS) that is activated by high glucose levels 59 and mechanical stretch. 60 In turn, activation of the podocyte RAS leads to an increase in podocyte apoptosis 60 and also to a reduction in the expression of nephrin. 61 Nephrin is a key component of the slit diaphragm, 52,61 a junction connecting the foot process of neighboring podocytes, which represents the major restriction site of protein filtration.…”
Section: In Vitro Studies Searching For the Mechanism Of The Interactmentioning
confidence: 99%